Cryptomelane-Type KMn8O16 as Potential Cathode Material — for Aqueous Zinc Ion Battery - Cui, Jiajie; Wu, Xianwen; Yang, Sinian; Li, Chuanchang; Tang, Fang; Chen, Jian; Chen, Ying; Xiang, Yanhong; Wu, Xianming; He, Zeqiang (Frontiers in Chemistry, 2018)
Aqueous battery has been gained much more interest for large-scale energy storage fields due to its excellent safety, high power density and low cost. Cryptomelane-type KMn8O16 confirmed by X-ray diffraction (XRD) was successfully synthesized by a modified hydrothermal method, followed by annealed at 400°C for 3 h. The morphology and microstructure of as-prepared KMn8O16 investigated by field-emission scanning electron microscopy (FE-SEM) with the energy spectrum analysis (EDS) and transmission electron microscopy (TEM) demonstrate that one-dimensional nano rods with the length of about 500 nm constitute the microspheres with the diameter about 0.5~2 μm. The cyclic voltammetry measurement displays that the abundant intercalation of zinc ions on the cathode takes place during the initial discharge process, indicating that cryptomelane-type KMn8O16 can be used as the potential cathode material for aqueous zinc ion batteries. The electrode shows a good cycling performance with a reversible capacity of up to 77.0 mAh/g even after 100 cycles and a small self-discharge phenomenon.